Diet and Hygiene in Modulating Autoimmunity During the Pandemic Era - Abdelhamid, Leila; Luo, Xin M. (Frontiers in Immunology, 2022)
The immune system is an efficiently toned machinery that discriminates between friends and foes for achieving both host defense and homeostasis. Deviation of immune recognition from foreign to self and/or long-lasting inflammatory responses result in the breakdown of tolerance. Meanwhile, educating the immune system and developing immunological memory are crucial for mounting defensive immune responses while protecting against autoimmunity. Still to elucidate is how diverse environmental factors could shape autoimmunity. The emergence of a world pandemic such as COVID-19 not only threatens the more vulnerable individuals including those with autoimmune conditions but also urges for extraordinary hygiene measures that likely contribute to the development or exacerbation of autoimmunity. There is an urgent need to understand how environmental factors modulate systemic autoimmunity. Here, we discuss the effects of diet (macronutrients and micronutrients) and hygiene (microbial infections, use of disinfectants) on autoimmunity with a focus on systemic lupus erythematosus.